Clinical management of the neonatal pneumomediastinum - Corsini, I.; Dani, C. (Acta Biomedica Atenei Parmensis, 2014)
pneumomediastinum (PM) occurs in approximately 0.1% of newborns but its incidence is underestimated because it is often asymptomatic. PM generally has a benign course. Our knowledge of PM is insufficient, and its management is mainly based on the best practice and experience of each hospital rather than on evidence-based data.